2022
DOI: 10.1152/ajpheart.00464.2022
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of remote ischemic conditioning is lost in patients with hypercholesterolemia

Abstract: Remote ischemic conditioning (RIC), brief repetitive cycles of ischemia and reperfusion in remote tissues, is known to induce robust protection against myocardial ischemia-reperfusion injury in preclinical studies. However, translation of the beneficial effects to the clinical setting has been challenging. A possibility is that co-morbidities, including hypercholesterolemia, interferes with the protective mechanisms of RIC. The aim of this study was to test if hypercholesterolemia attenuates the efficacy of RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In contrast, another study consisting of 24 patients observed that RIC protected from endothelial dysfunction induced by forearm ischemia-reperfusion in healthy controls (flow-mediated vasodilation (FMD) baseline 2.8 ± 2.3 vs. FMD after I/R + RIC 4.5 ± 4.0%; means SD) and in patients with familial hypercholesterolemia (FH) with low LDL-C (4.5 ± 3.5 vs. 4.4 ± 4.2%). However, RIC was ineffective in patients with FH and high LDL-C (FMD 3.9 ± 3.0 vs. 1.1 ± 1.5%; p < 0.01) [33]. In addition, statins are also known to blunt the effect of RIC, and this may have further attenuated the effects in the intervention arm [34].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study consisting of 24 patients observed that RIC protected from endothelial dysfunction induced by forearm ischemia-reperfusion in healthy controls (flow-mediated vasodilation (FMD) baseline 2.8 ± 2.3 vs. FMD after I/R + RIC 4.5 ± 4.0%; means SD) and in patients with familial hypercholesterolemia (FH) with low LDL-C (4.5 ± 3.5 vs. 4.4 ± 4.2%). However, RIC was ineffective in patients with FH and high LDL-C (FMD 3.9 ± 3.0 vs. 1.1 ± 1.5%; p < 0.01) [33]. In addition, statins are also known to blunt the effect of RIC, and this may have further attenuated the effects in the intervention arm [34].…”
Section: Discussionmentioning
confidence: 99%
“… 8 A recent study did not find the protective effect of RIC on ischemia–reperfusion injury‐induced endothelial dysfunction in patients with familial hypercholesterolemia with elevated LDL‐C. 9 Two small clinical studies reported that the cardioprotective effect of ischemic postconditioning was lost in the patients with coronary artery disease with higher cholesterol. 10 , 11 In addition, numerous animal experiments have revealed that hypercholesterolemia may interfere with the cardioprotective potential of ischemic conditioning.…”
mentioning
confidence: 99%